2009
DOI: 10.3892/ijo_00000477
|View full text |Cite
|
Sign up to set email alerts
|

Target chemotherapy of anti-CD147 antibody-labeled liposome encapsulated GSH-DXR conjugate on CD147 highly expressed carcinoma cells

Abstract: Abstract. It was confirmed that CD147 (Emmprin) was expressed on the cell surface of carcinoma cells. For the purpose of studying the efficacy of a CD147-targeting agent on CD147-expressing carcinoma cells, we investigated the effect of a conjugate of glutathione-doxorubicin (GSH-DXR) encapsulated in an anti-CD147 antibody-labeled liposome (aCD147ab-liposome) in terms of specific accumulation and cytotoxicity in CD147-expressing human carcinoma cells. Expression of CD147 was not observed in many normal human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Recently, Dean et al [43] demonstrated treatment with anti-CD147 MAb delayed tumor growth in a mouse model of head and neck cancer compared with untreated controls and increased sensitivity of radiation therapy. Using a conjugate of glutathione-doxorubicin (GSH-DXR) encapsulated in an anti-CD147 antibodylabeled liposome (aCD147ab-liposome), Matsudaira et al [44] recently demonstrated that this target chemotherapy conjugate can effectively target CD147-positive cancer cells in vitro. An anti-tumor potential of MCT1 inhibition was most recently supported by a reduction of tumor growth in in vivo models of lung carcinoma, colorectal carcinoma and a squamous carcinoma cell line after acyano-4-hydroxycinnamate-mediated MCT1 inhibition [45].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Dean et al [43] demonstrated treatment with anti-CD147 MAb delayed tumor growth in a mouse model of head and neck cancer compared with untreated controls and increased sensitivity of radiation therapy. Using a conjugate of glutathione-doxorubicin (GSH-DXR) encapsulated in an anti-CD147 antibodylabeled liposome (aCD147ab-liposome), Matsudaira et al [44] recently demonstrated that this target chemotherapy conjugate can effectively target CD147-positive cancer cells in vitro. An anti-tumor potential of MCT1 inhibition was most recently supported by a reduction of tumor growth in in vivo models of lung carcinoma, colorectal carcinoma and a squamous carcinoma cell line after acyano-4-hydroxycinnamate-mediated MCT1 inhibition [45].…”
Section: Discussionmentioning
confidence: 98%
“…The ligand of scFv-M6-1B9 is M6, also called CD147 [38,39], a transmembrane glycoprotein highly expressed in various types of malignant cells [57] and tumors, e.g. nasopharyngeal carcinoma [58].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been expended on this approach; the most popular ligands are monoclonal antibodies or Fab fragments specific to tumor cell antigens [94-96], peptide [97], folate [98], and transferrin [99,100]. Most of these ligands are internalized by the clathrin-mediated endocytosis and are therefore subjected to the same considerations and limitations (see below).…”
Section: Np Cellular and Subcellular Compartments Targetingmentioning
confidence: 99%